In Vivo Evaluation of Tissue Biocompatibility of Calcium Silicate-based and Epoxy Resin-based Sealers - Candeiro, George Táccio de Miranda; Magalhães, Amanda Kevys; Sousa Evangelista, Laissa; Brito Santos, Amanda; Bernardo Dantas, Larissa; Camelo Paiva, Hermano; Gavini , Giulio; Goberlânio de Barros Silva, Paulo (Iranian Endodontic Journal, 2024)
Introduction: Calcium silicate-based sealers are an alternative to be used into root canal, mainly to their biological properties. However, some biological parameters need to be determined in an in vivo animal research model. So, the aim of the present study was to evaluate in vivo the tissue biocompatibility of a calcium silicate-based sealer (EndoSequence BC Sealer) and an epoxy resin-based sealer (AH-Plus). Materials and Methods: Polyethylene tubes were filled with freshly mixed sealers and implanted in connective subcutaneous tissue of 25 rats (5/euthanasia day) (Rattus norvegicus albinus). Empty tubes were used as controls and no tubes as sham. Histopathological (hematoxylin eosin) and histochemical (Picrosirius red) examinations were conducted at 3, 7, 15, 30 and 60 days (five rats/day) after the implantation procedure (n=5/group). The type/intensity of inflammation and collagenesis was analyzed statistically with Friedman or Kruskal-Wallis/Dunn tests (P<0.05). Results: The profile of inflammation induced by AH-Plus (Median=2, Range=2-3) was significantly greater than that by Endosequence BC Sealer (Median=1, Range=1-1) during the 15-day experimentation period (P=0.018). After 30 days, both materials produced similar tissue reaction (P>0.05). AH-Plus and Endosequence BC Sealer (Median=2, Range=1-2) induced a high level of fibrosis after 60-day than control (Median=1, Range=1-1) and sham (Median=0, Range=0-0) groups (P<0.001) of fibrosis based in type I collagen increase (P=0.025 and P=0.021, respectively). Tissue necrosis was not observed and the bioceramic sealer showed significant signs of endocytosed (Median=1, Range=1-1) material after 7 days than other groups (Median=0, Range=0-0) (P<0.05). The calcium silicate-based sealer induced tissue repair faster than the epoxy resin-based sealer tested. However, both materials showed adequate biocompatibility and tolerance by subcutaneous tissues, with few differences in inflammatory profiles, formation of granulation tissue, and collagenesis. Conclusions: It may be concluded that calcium silicate-based sealer (EndoSequence BC Sealer) and an epoxy resin-based sealer (AH-Plus) presented suitable biocompatibility.